In vivo monitoring of Ca2+ uptake into subcellular compartments of mouse skeletal muscle - Rudolf, Rüdiger (Calcium signalling, 2019)
Ca2+ regulates many functions of skeletal muscle, including excitation-contraction coupling, energy homeostasis, and fiber-type-specific gene expression. However, microscopic observation of Ca2+ signalling in live skeletal muscle tissue has been hampered, in particular, by the combination of the high speed of Ca2+ transients and the contractile properties that are inherent to muscle. The present chapter describes methods to visualize Ca2+ signals during relaxation-contraction cycles in different subcellular compartments at high spatiotemporal resolution or at the global muscle level in combination with simultaneous measurements of muscle force. These protocols employ transfection of genetically encoded ratiometric Ca2+ sensors and two-photon microscopy as well as force transducers and associated hardware for data acquisition. Information on how to determine subcellular localization of the genetically encoded Ca2+ sensors and on how to calibrate the ratiometric data in a semiquantitative manner is given in the final paragraphs.
Im Titel ist "2+" hochgestellt
Gesehen am 03.07.2020